Improved lignocellulolytic enzyme production and antioxidant extraction using solid‐state fermentation of olive pomace mixed with winery waste. (23rd December 2019) - Filipe, Diogo; Fernandes, Helena; Castro, Carolina; Peres, Helena; Oliva‐Teles, Aires; Belo, Isabel; Salgado, José M.
Abstract: Olive pomace is characterized by its low nutritional value and high phenolic content, which hinders its direct use as animal feed, fertilizer, or as a substrate in bioprocesses such as solid‐state fermentation (SSF). A possible strategy for bioprocessing olive pomace by SSF is the mixture of olive mill wastes with other wastes produced in the same region, such as winery wastes. This may improve the production of bioactive compounds like enzymes and antioxidant phenolics. A simplex‐centroid design was used to evaluate the use of olive mill and winery wastes alone or in combination as a substrate for SSF with Aspergillus niger and Aspergillus ibericus . Synergistic effects of combinations of crude olive pomace (COP), exhausted olive pomace (EOP), vine trimming shoots (VTS), and exhausted grape marc (EGM) were observed in the production of xylanases, cellulases, β ‐glucosidases, and in the variation in total phenolics and antioxidant activity of SFF extracts. A multiple response optimization was carried out, leading to the following optimal mixture of substrates: for A. niger, 23% (w/w) COP, 30% EGM, 33% VTS, 14% EOP; for A. ibericus, 30% EGM, 36% VTS, 34% EOP. The scale‐up to tray bioreactor with optimal substrate made it possible to achieve the maximum xylanase, cellulase, and β ‐glucosidase production of 189.1 ± 26.7, 56.3 ± 2.1 and 10.9 ± 0.8 U/g, respectively. The antioxidant activity of fermented wastes was also improved 2.2‐fold as compared with unfermented wastes. Thus, a combination of olive mill and winery wastes in SSF is a potential strategy to increase their value and to develop a circular strategy in these industries. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.